La presse et la politique étrangère canadienne - Keenleyside, T.A.; Burton, B.E.; Soderlund, W.C. (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
This article reports on the findings of what appears to be the first content analysis of all aspects of Canadian press coverage of Canadian foreign relations. Six major/newspapers were chosen on the basis of national significance and linguistic and regional considerations: the Halifax Chronicle-Herald, Le Devoir (Montréal), La Presse (Montréal), the Ottawa Citizen, the Toronto Globe and Mail and the Vancouver Sun. During the period studied (the last quarter of 1982), these newspapers averaged nearly nine items per issue on Canadian foreign relations and relied predominantly on Canadian sources for their material. However, there was a relative lack of analytic coverage and only a limited number of items that adopted supportive or critical positions on the various issues in Canadian foreign policy. Commercial matters received both the most extensive and the most sophisticated treatment, while the reporting of political subjects was generally less detailed and often superficial. In terms of relationships, that with the United States was arguably the only one to receive adequate coverage, while from the standpoint of issues there were several that received insufficient attention, such an environmental problems in relations with the United States, Canadian concerns at the United Nations, and international developmental matters. One of the most notable differences in coverage among the papers studied was the variation found in the attention paid to the international role of Quebec, which received only scant attention in the English-language press but was the single most frequently coded theme in the Quebec newspapers. While analytic coverage was found to be more extensive and profound in the Globe and Mail, Le Devoir and La Presse than in the other three papers, the authors in general agree with De Montigny Marchand that Canadian newspapers are "an uncertain intellectual force in the definition and interpretation of Canadian foreign policy".